Estudos de musicoterapia improvisacional musicocentrada e desenvolvimento musical de crianças com autismo - Marina Horta Freire (2019)
Music-centered Improvisational Music Therapy is a music therapy approach that works with the individual musicality conveyed through musical coactive improvisation towards treatment of children with autism, regarding to promote communicativeness and socialinteraction improvement. Musical development is an important indicator of human development, which also involves communication and interaction, that may influence as well be influenced by music therapeutic process. This current thesis aims to investigate the relations between Music-centered Improvisational Music Therapy and the musical development of children with autism. Hence, four independent studies relates to the theme are shown here. The first study consists of literature revision about musical development of people with autism treated by music therapists and a reported case of a child with autism during sessions of Music-centered Improvisational Music Therapy, which demonstrates the lack of publication about the theme and the possibility to assess the musical development in the music therapeutic process. Considering the justifications that allow understanding the musical-cognitive development of children with autism onto Improvisational Musiccentered Music Therapy, the second study investigates interfaces between Communicative Musicality theory and the Nordoff-Robbins Music Therapy Approach, from Edward studycase, a child with autism treated by the creators of this approach, who describe the spontaneous musical exchanges on the clinical music improvisation in a similar manner towards the characteristics described on the Communicative Musicality theory. The third study investigates the validity evidences of the Music Development of Children with Autism Scale (MUDECA Scale), through semantic analyses, inter-examiners, internal consistence and external reliability, and shows results that indicate the use of MUDECA Scale in Brazil. Ultimately, the fourth study has presented a quantitative investigation that assessed the initial and final musical development of 25 children with autism during Music-centered Improvisational Music Therapy treatment, through MUDECA Scale, and correlated this musical development to therapeutic gains (previous collected data), emphasizing the heightening level of musical development of the children assessed after treatment as well as important correlations between the musical development and the improvement of communication, discussed under the perspective of Communicative Musicality theory. By considering these studies taken, it was possible to observe, qualitative and quantitatively, the relevance of the relationships between the musical development and Music-centered Improvisational Music Therapy, which contribute to interdisciplinary knowledge in the fields of Music Therapy, Musical Education and Health.